Internalization of Islamic Communication Ethics in Forming Wise Attitudes in Using Social Media in Instagram Users - Nanda Nasution, Anggun Dwi; Fauzi Wirahyuda; Rubino (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
This article discusses the process of internalizing Islamic communication ethics in shaping wise social media behavior among Instagram users, a platform that has now become a digital public space with complex interaction dynamics. In the context of the increasing spread of unverified information, hate speech, and the often-dominant culture of showing off, Islamic communication ethics is seen as a normative foundation capable of guiding more responsible and civilized social media behavior. This research uses a qualitative approach with a library study method, reviewing various literature on the principles of Islamic communication ethics such as honesty, caution, tabayyun (reconciliation), maintaining the honor of oneself and others, and avoiding gossip and slander. The analysis is conducted by examining how these values ​​can be implemented in everyday communication practices on Instagram. The study's findings indicate that internalizing Islamic communication ethics can foster more constructive interaction patterns, encouraging users to verify information before sharing, avoid negative comments, and practice polite language. The discussion reveals that transforming user behavior depends not only on an understanding of ethical values, but also on self-awareness, personal control, and a supportive digital environment. This internalization plays a crucial role in building a more humanistic and welfare-oriented social media culture. In conclusion, the application of Islamic communication ethics has proven relevant and effective in shaping the wise behavior of Instagram users. These ethical values ​​can serve as moral guidelines for facing the challenges of modern digital communication, while also strengthening positive character traits in online interactions.